Analisis Pengalaman Pengguna Aplikasi ShopeePay: Implementasi Metode UEQ untuk Optimalisasi Layanan - Chika Prasida Nabil Yahya; Sigit Sugiyanto (Jurnal Teknologi Informasi dan Multimedia, 2025)
ShopeePay is one of the e-wallet applications that is widely used in Indonesia thanks to its various benefits, convenience, and security in digital transactions. However, the quality of user experi-ence still requires in-depth analysis so that this application can meet the evolving needs of users. This study uses the User Experience Questionnaire (UEQ) method to assess six main dimensions, namely attractiveness, clarity, efficiency, accuracy, stimulation, and novelty. The analysis showed that attractiveness (1.15), clarity (1.27), and efficiency (1.14) were above average when compared to global standards. However, accuracy (0.98), stimulation (0.75), and novelty (0.67) were below average, highlighting the need for improvement in the aspects of innovation and emotional en-gagement of users. By understanding the strengths and weaknesses in each of these dimensions, this study provides recommendations for improvements to enhance the quality of the app. Up-dates in the dimensions of fidelity, stimulation, and sustainability are expected to increase user satisfaction while strengthening their loyalty to the app. These findings are not only useful for Shopee Pay developers but can also serve as a reference for the development of other e-wallet apps to remain competitive in the digital market. Overall, user experience optimization is an important element in maintaining app competitiveness and meeting user expectations in this era.